A phase 2 study of lenalidomide and dexamethasone in previously untreated patients with chronic lymphocytic leukemia (CLL). Issue 4 (21st March 2019) - Chen, Christine I.; Paul, Harminder; Snitzler, Susi; Kakar, Sumeet; Le, Lisa W.; Wei, Ellen N.; Lau, Anthea; Johnston, James B.; Gibson, Spencer B.; Queau, Michelle; Spaner, David; Croucher, Danielle; et al.
Abstract: Lenalidomide has anti-tumor activity in CLL but can be complicated by tumor lysis syndrome (TLS) and tumor flare (TF). In our previous study using low-dose lenalidomide in treatment-naive CLL, TLS was averted but TF remained frequent and complete responses (CR) were rare, despite treatment to progression. The addition of dexamethasone may mitigate TF and enable lenalidomide dose escalation, achieving durable response without long-term use. In this phase 2 trial, 31 treatment-naive CLL patients received lenalidomide (target 25mg daily) plus dexamethasone for a finite 18 cycles. No patients developed TLS and TF was infrequent. Overall responses were 74.2% (CR 9.7%) and median progression-free survival 27 months. Cereblon-binding proteins IKZF1 and IKZF3 were largely downregulated, with associated increased IRF4 levels. We therefore report that lenalidomide plus dexamethasone can achieve durable responses in a subset of patients without continuing therapy until progression. Upregulation of IRF4 may contribute to anti-CLL activity of immunomodulatory agents. This trial was registered at www.clinicaltrials.gov as NCT01133743.